Carotid body plastic behavior: evidence for D2–H3 receptor–receptor interactions - Stocco, Elena; Emmi, Aron; Sfriso, Maria Martina; Tushevski, Aleksandar; De Caro, Raffaele; Macchi, Veronica; Porzionato, Andrea (Frontiers in Physiology, 2024)
Dopamine and Histamine receptors D2R and H3R are G protein-coupled receptors (GPCRs) which can establish physical receptor-receptor interactions (RRIs) leading to homo/hetero-complexes in a dynamic equilibrium. While D2R and H3R expression has been detected within the carotid body (CB), their possible heterodimerization has never been demonstrated. The aim of this work was to verify D2R and H3R colocalization in the CB, thus suggesting a possible interplay that in turn may be responsible of specific D2R-H3R antagonistic functional implications. The CBs of both Sprague Dawley rats (n=5) and human donors (n=5) were dissected and immunolocalization of D2R and H3R was performed; thereafter, in situ proximity ligation assay (PLA) was developed. According to experimental evidences (immunohistochemistry, double immunofluorescence), all the samples displayed positive D2R/H3R elements; hence, PLA assay followed by confocal microscopy analysis was positive for D2R-H3R RRIs. Additionally, D2R-H3R heterodimers were mainly detected in type I cells (βIII-tubulin positive cells) but type II cells involvement cannot be excluded. RRIs may have a role in CB cells functional modulation; investigating RRIs in the CB may guide towards comprehension of its plastic-changes and fine regulatory role, also unveiling their possible clinical implications.